1978
DOI: 10.1002/j.1537-2197.1978.tb10828.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems in the Identity and Origin of the Appalachian Vittaria Gametophyte, a Sporophyteless Fern of the Eastern United States

Abstract: Populations of a fern gametophyte presumed to be of the genus Vittaria occur commonly in the uplands of the southeastern United States. The gametophytes occur on non‐calcareous rock outcrops of various composition in areas which provide continuous moisture and protection from temperature extremes. Gametophytes in these habitats are robust and long lived, frequently forming the dominant vegetation in areas covering several square feet. Reproduction is exclusively vegetative by production of gemmae. Although sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 14 publications
1
54
0
Order By: Relevance
“…Among the taxa examined in our study, the strongest evidence for ancient asexuality is in Vittaria appalachiana, where patterns of geographical distribution and genetic diversity indicate an age of at least 10 million years (Farrar 1967(Farrar , 1978(Farrar , 1990. A study of allozyme diversity in Vittaria showed V. appalachiana to have no recent origin from or close relation to sexual Vittaria species (Farrar 1985(Farrar , 1990.…”
Section: Possible Explanations For the Pattern Of Conserved Te Sequenmentioning
confidence: 71%
“…Among the taxa examined in our study, the strongest evidence for ancient asexuality is in Vittaria appalachiana, where patterns of geographical distribution and genetic diversity indicate an age of at least 10 million years (Farrar 1967(Farrar , 1978(Farrar , 1990. A study of allozyme diversity in Vittaria showed V. appalachiana to have no recent origin from or close relation to sexual Vittaria species (Farrar 1985(Farrar , 1990.…”
Section: Possible Explanations For the Pattern Of Conserved Te Sequenmentioning
confidence: 71%
“…To date, all independent gametophytes to which species names have been assigned (not an easy task -see Farrar (1978) and below) are members of three families; the Hymenophyllaceae, Grammitidaceae and the Vittariaceae, but it is not yet clear whether gametophytic independence is characteristic of these families or of only certain genera or species within them. Currently, independent gametophytes are known: in nine species of the Hymenophyllaceae in four genera (Hymenophyllum, Mecodium, Trichomanes, and Callistopteris); in the Grammitidaceae one species in one genus (Grammitis, Xiphopteris or Micropolypodium, depending on one's view-point); and in the Vittariaceae two species in one genus (Vittaria).…”
Section: Independent Gametophytesmentioning
confidence: 99%
“…The reasons for believing this are three-fold: First, all the gametophytes of Vittariaceae for which at least some published morphological data is available (18 species representing the genera Ananthacorus, Anetium, Hecistopteris, Vittaria, Radiovittaria, Haplopteris, Antrophyum, Polytaenium, Scoliosorus, and Vaginularia;see Goebel 1888see Goebel , 1896Britton & Taylor 1902;Troll 1932;Stokey 1951;Atkinson & Stokey 1964;Farrar 1974Farrar , 1978and Crane 1997) are ribbon-shaped with multiple marginal meristems that frequently dichotomize (gametophytes of most fern species are heart-shaped, unless old or damaged, with a single recessed apical notch meristem). These features are consistent with a creeping, branching, mat or weftforming habit and a perennial existence.…”
Section: Independent Gametophytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In northeastern United States, gametophytes of the genus Vittaria Sm. can become established in certain environments, form extensive populations through asexual reproduction by apogamy and persist during prolonged frost while the sporophytes do not survive, dying at the beginning of their development (Farrar 1978). These reports were also corroborated by Sato & Sakai (1980) for many Asiatic species, where the gametophytic phase can resist temperatures below -40°C, while their sporophytes do not survive in temperatures below 0°C.…”
Section: Discussionmentioning
confidence: 80%